Paediatric Sialorrhoea - Sulaiman, Golya; Mahroos, Ahmad Al Ghabban; Othman, Ahmad; Siddiqui, Emad Uddin (Journal of the Pakistan Medical Association, 2026)
Sialorrhoea is a rare but disturbing symptom associated with increased salivary secretions which may burden the family and the child, and can affect both the patient’s and family’s psychological well-being, emotionally and physically. The reasons may be abnormal neuromuscular control, swallowing coordination defects etc. Rarely oral, dental and gingival problems like inflammation, caries, malocclusion may also cause increased salivary secretion. We present a unique case of hypersalivation lasting for two weeks without a clear history of dental or oral illness, any drug exposure, or any chronic disease. Management is based on a multidisciplinary team approach, with treatment options ranging from conservative measures like simple observation, neck positioning, behavioural and pharmacological therapies to botulinum toxin or surgery. The patient may need to consult a dentist or orthodontist to assess the extent of secretion and to determine any medical or surgical cause. Key words: Sialorrhoea, Paediatric, Management.